The Christmas cookie collection - Wilde, Lori. (Avon, an imprint of HarperCollinsPublishers, New York, New York, 2013)
There's a legend in Twilight, Texas. It says that if on Christmas you sleep with kismet cookies under your pillow and dream of your one true love, he will be your destiny.
Carrie -- Raylene -- Christine -- Grace.
Keywords: Cookies -- Fiction; Man-woman relationships -- Fiction; Love stories; Christmas stories; Texas -- Fiction